Long-term athlete development for parents (2015)
Many parents are looking for answers to explain what is right for their child when it comes to athletic development. As a coach, you need something that will help explain the facts in an easy, accurate, and user-friendly manner. The Coaching Association of Canada, in coordination with Canadian Sport for Life, has created the following document: "Long-Term Athlete Development Information for Parents" to help coaches educate the parents of the children in their programs.